Occurrence of contaminants of emerging concern (CECs) in surface waters and wastewater in Johor, Malaysia - Yuen, Jia Wei (Nanyang Technological University, 2021)
Increased awareness of synthetic chemicals in the aquatic environment have resulted in them being labelled as contaminants of emerging concern (CECs). However, the occurrence of CECs in developing countries, such as Malaysia, is limited. There, wastewater from agriculture and industries is often untreated and quietly discharged into water bodies without regard for aquatic ecosystems and other downstream water users. In the first part of this study, the occurrence of CECs along the main river and tributaries of the Johor River Basin (JRB) was determined. To evaluate the extent of CEC contamination, water samples were collected from five rivers outside the JRB and ten wastewater treatment plants in Southern Johor. Using solid phase extraction (SPE) coupled with liquid chromatography tandem mass spectrometry (LC-MSMS), 25 commonly used CECs (15 pharmaceuticals, 6 pesticides, 3 personal care products, and 1 stimulant) were determined. In JRB, diclofenac (4.52 – 130.54 ng L-1), diphenhydramine (2.50 – 32.37 ng L-1), ametryn (0.95 – 545.25 ng L-1), caffeine (20.33 – 1005.04 ng L-1), and DEET (8.56 – 1005.04 ng L-1) were present in all the sampled rivers. Similarly, Acetaminophen (2.56 – 924.40 ng L-1), carbamazepine (0.27 – 21.73 ng L-1), diphenhydramine (0.60 – 13.40 ng L-1), gemfibrozil (4.02 – 84.56 ng L-1), metoprolol (4.09 – 237.74 ng L-1), naproxen (7.28 – 127.63 ng L-1), perindopril (2.53 – 17.57 ng L-1), caffeine (40.51 – 11034.99 ng L-1) and DEET (20.61 – 303.22 ng L-1) were detected in the five rivers outside the JRB. Notably, seven CECs (diphenhydramine, naproxen, gemfibrozil, ametryn, atrazine, methomyl, and fenobucarb) were previously undetected in previous studies in Malaysia. In addition, CECs such as acetaminophen, atenolol, carbamazepine, diclofenac, gemfibrozil, ibuprofen, metoprolol, caffeine, DEET, and triclosan were also found in wastewater effluents of at least five wastewater treatment plants. Overall, acetaminophen, atrazine, methomyl, and DEET showed moderate risks to aquatic ecosystems (RQ = 0.10 to 0.56), while ametryn, chlorpyrifos, and caffeine posed a high risk (RQ = 1.71 to 149). In the second part of the study, ion suppression in a non-targeted analysis (NTA) workflow was evaluated at various dilution factors (1, 2, 4, and 10) on the liquid chromatography-quadrupole time-of-flight (LC-QTOF). Additional compounds absent in the undiluted samples were detected in diluted samples, highlighting the presence of ion suppression. However, the analyte signals in the diluted samples did not decrease proportionately with dilution factors, showing signs of ion suppression even with dilution. The samples were also analysed on the LC-MSMS based on a selected list of 26 CECs. Targeted analysis detected 18 compounds, while NTA only detected 10, highlighting that ion suppression affects the sensitivity of NTA and may cause risk adverse CECs to be undetected. Thus, analysing samples at various dilution factors can help improve the sensitivity in NTA.